Past for the Eyes - Oksana Sarkisova, Péter Apor (Central European University Press, 2008)
How do museums and cinema shape the image of the Communist past in today's Central and Eastern Europe? This volume is the first systematic analysis of how visual techniques are used to understand and put into context the former regimes. After history "ended" in the Eastern Bloc in 1989, museums and other memorials mushroomed all over the region. These efforts tried both to explain the meaning of this lost history, as well as to shape public opinion on their society's shared post-war heritage...